2014
DOI: 10.1038/nature13036
|View full text |Cite
|
Sign up to set email alerts
|

Developmental pathway for potent V1V2-directed HIV-neutralizing antibodies

Abstract: Summary Antibodies capable of neutralizing HIV-1 often target variable regions 1 and 2 (V1V2) of the HIV-1 envelope, but the mechanism of their elicitation has been unclear. Here we define the developmental pathway by which such antibodies are generated and acquire the requisite molecular characteristics for neutralization. Twelve somatically related neutralizing antibodies (CAP256-VRC26.01-12) were isolated from CAPRISA-donor CAP256; each antibody contained the protruding tyrosine-sulfated, anionic antigen-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
1,073
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 695 publications
(1,139 citation statements)
references
References 82 publications
39
1,073
1
2
Order By: Relevance
“…CAP256 was infected with a clade C TF virus and superinfected with a second clade C TF ~15 weeks after primary infection (63). The CAP256-VRC26 lineage was initiated by the superinfecting virus and the CAP256-VRC26.UCA was likely engaged by modestly mutated viruses (19, 64). …”
Section: Antibody-virus Co-evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAP256 was infected with a clade C TF virus and superinfected with a second clade C TF ~15 weeks after primary infection (63). The CAP256-VRC26 lineage was initiated by the superinfecting virus and the CAP256-VRC26.UCA was likely engaged by modestly mutated viruses (19, 64). …”
Section: Antibody-virus Co-evolutionmentioning
confidence: 99%
“…The B cell lineage immunogen design strategy is based on mapping the co-evolution of autologous virus and neutralizing lineages over time to select Env variants of the autologous virus quasispecies that participated in the selection of bnAb precursors by progressively engaging bnAb precursors, starting with the UCA and selection of immunogens with characteristics of Envs involved in natural induction of bnAbs in vivo (1619, 64) (Korber, Hraber, Wagh and Hahn, this volume).…”
Section: B Cell Lineage Immunogen Designmentioning
confidence: 99%
“…Longitudinal sampling of the antibodyome provides temporal resolution of antibody repertoire dynamics and of B‐cell ontogenies6, 7, 18 (Fig. 3A–C).…”
Section: Antibodyomics2mentioning
confidence: 99%
“…We have also used Antibodyomics2 to investigate the origins of the CAP256‐VRC26 lineage, a V1V2‐targeting broadly neutralizing antibody 6, 19. We were able to identify autologous viruses that likely helped trigger lineage development and showed that toleration of early autologous escape mutants correlates strongly with the acquisition of breadth 19.…”
Section: Antibodyomics2mentioning
confidence: 99%
See 1 more Smart Citation